Bi-Polar Bioenergetic Intervention via a Pathology Self-Adaptive Single-Atom Nanocatalyst for Diabetic Tumor Postoperative Management - Chen, Jiajie; Huang, Jimin; Yang, Zhibo; Tang, Kai; Wu, Chengtie; Ye, Huamao; Shi, Jianlin; Zhu, Yufang (Nano-Micro Letters, 2026)
Diabetes aggravates postoperative tumor recurrence and impairs wound healing due to divergent metabolic adaptations to hyperglycemia in tumor versus normal cells. Current therapeutics fail due to the incapabilities in adaptively modulating the metabolic bifurcation across the contradictory pathological contexts. Here, we address this challenge by developing a platinum (Pt) single-atom nanocatalyst (PtSNC) with microenvironments-selective multienzyme-mimicking activities to pioneer a bi-polar bioenergetic intervention strategy. In acidic and reduced nicotinamide adenine dinucleotide (NADH)-overexpressed tumor niches, it exhibits NADH oxidase (NOX)-, oxidase-, and peroxidase-like activities, depleting NADH reserves and generating highly reactive Pt = O species to disrupt energy metabolism and induce both apoptosis/ferroptosis. While it shows NOX-, catalase-, and superoxide dismutase-like activities in neutral diabetic wounds, rectifying hyperglycemia-induced cellular NAD+/NADH abnormity and bioenergetic disorder to revitalize the cells and tissues, with promoting angiogenesis and mitigating local inflammation to accelerate regeneration. Murine diabetic melanoma resection models demonstrate its extensive capacity in effectively eradicating residual tumor tissues and suppressing the recurrence, and promoting diabetic wound healing concurrently without systemic toxicity, making PtSNC a safe and potent nanotherapeutic for diabetic tumor postoperative therapy. This study holds promise for the application of single-atom catalytic medicines in precision therapy for intractable diseases featuring pathological metabolic bifurcation. Highlights: 1 A high-density and well-structured platinum single-atom nanocatalyst (PtSNC) with pathological contexts-selective multienzyme-mimicking activities is developed to pioneer a bi-polar bioenergetic intervention strategy and break the hyperglycemia-induced metabolic paradox. 2 The PtSNC disrupts energy metabolism and triggers ferroptosis/apoptosis via depleting nicotinamide adenine dinucleotide (NADH) reserves and producing highly reactive Pt = O species in tumor niches, but rectifies cellular NAD+/NADH abnormity and bioenergetic disorder in diabetic wounds, offering a promising solution to diabetic tumor postoperative therapy.